Genotypic and phenotypic correlations of biotinidase deficiency in the Chinese population - Rai-Hseng Hsu; Yin-Hsiu Chien; Wuh-Liang Hwu; I-Fan Chang; Hui-Chen Ho; Shi-Ping Chou; Tzu-Ming Huang; Ni-Chung Lee (Orphanet Journal of Rare Diseases, 2019)
Abstract Biotinidase deficiency is an autosomal recessive disorder that affects the endogenous recycling and release of biotin from dietary protein. This disease was thought to be rare in East Asia. In this report, we delineate the phenotype of biotinidase deficiency in our cohort. The genotypes and phenotypes of patients diagnosed with biotinidase deficiency from a medical center were reviewed. The clinical manifestations, laboratory findings, and molecular test results were retrospectively analyzed. A total of 6 patients were evaluated. Three patients (50%) were diagnosed because of a clinical illness, and the other three (50%) were identified by newborn screening. In all patients, the molecular results confirmed the BTD mutation. The three patients with clinical manifestations had an onset of seizure at the age of 2 to 3 months. Two patients had respiratory problems (one with apnea under bilevel positive airway pressure (BiPAP) therapy at night, and the other with laryngomalacia). Hearing loss and eye problems were found in one patient. Interestingly, cutaneous manifestations including skin eczema, alopecia, and recurrent fungal infection were less commonly seen compared to cases in the literature. None of the patients identified by the newborn screening program developed symptoms. Our findings highlight differences in the genotype and phenotype compared with those in Western countries. Patients with biotinidase deficiency benefit from newborn screening programs for early detection and management.